Linguistics of the English Language and its Structural Components - G’aybullayev Otabek; Kilicheva Vasila (Zien Journals, 2022)
The article says that language stands out among other phenomena of reality. Some branches of linguistics are listed.
Keywords: linguistics; English; student; teacher